Effectiveness of human papillomavirus HPV vaccination in primary prevention of cervical cancer - Bąk, Beata; Wrześniewska, Marzena (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Preventive vaccinations against Human Papillomavirus (HPV) are worldwide unique preparations developed for the protection against cervical cancer - the second most prevalent malignant disease that is the principal cause of death among women in terms of all cancer types. Although well-developed secondary prevention programs involving cervical cytology screening have contributed to the reduction of the cervical cancer mortality rate, yet their results as compared with possibilities they offer leave much to be desired. HPV infection is usually short-term, yet persistent HPV infection, especially related to viruses characterised by a high oncogenic potential, is closely connected with cervical cancer development and preneoplastic changes. Currently, there are two types of preventive vaccination available on the market — quadrivalent and bivalent one whose long-term effectiveness was confirmed by international randomised clinical tests. The tests proved 100% effectiveness of HPV infection prevention in seronegative women before starting a vaccination cycle. It is assumed that long-term possible benefits resulting from the vaccination against HPV will make cervical cancer mortality rate fall by approx. 70% in 15–20 years. Furthermore, the reduction of costly medical procedures related to antineoplastic treatment and therapy of psychological effects of medical treatment cannot be overlooked, either. There are no financial benefits or indeed any financial connections between the authors of this article and the products that are included in it.